Synchrotron-based crystal structure, associated morphology of snail and bivalve shells by X-ray diffraction - schiavon, nicola (2017)
Synchrotron-basedhigh-resolutionX-raypowderdiffractionspectrafromthebodypartsofasnailand bivalve(CaCO3), havebeenrecordedwithPilatusareadetector.ExperimentswereperformedatDesy, Hamburg, Germany,utilizingtheResonantandDiffractionbeamline(P9),with15keVX-rays (λ¼0.82666Å).Theexternalshelloftheselivingorganisms,iscomposedofcalciumcarbonate,which carries strongbiologicalsignal.Itconsistsofsomelightelements,suchas,Ca,CandO,whichconstitute part ofthesofttissueandothertraceelements.Theknowledgeofthesediffractionpatternsandhence the understandingofstructuresatmolecularlevelareenormous.Theapplicationofsynchrotronra- diation topowderdiffractioniswellsuitedforsamplesofbiologicalnatureviachangesintheirpatterns and alsotoinvestigatecrystallographicphasecomposition.WiththeuseofRietveldrefinement proce- dure, tothehigh-resolutiondiffractionspectra,wewereabletoextractthelatticeparametersofor- thorhombic polymorphofCaCO3, themostabundantmineralproducedbytheselivingorganisms.The small sizeofthecrystalliteisaveryimportantfactorrelatedtothebiologicalstructure.Thenatural model presentsacombinationoforganicandinorganicphaseswithnanometersize.Forthepresent study,wealsousedthescanningelectronmicroscopy(SEM)toexploretheassociatedmorphologyofthe snail andbivalve.